1990
DOI: 10.1161/01.str.21.9.1262
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in stroke incidence in Hisayama, Japan.

Abstract: We investigated seasonal variation in the incidence of cerebral stroke among the general population aged >40 years in November of 1961 in Hisayama, Japan. During the 24-year follow-up period, 311 cases of cerebrovascular diseases occurred. The date or month of onset was determined in 308 cases, of which 51 were classified as intracerebral hemorrhage, 223 as cerebral infarction, and 27 as subarachnoid hemorrhage. We observed a significant seasonality in the incidence of all stroke (p<0.01), of intracerebral hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
139
5
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(172 citation statements)
references
References 26 publications
22
139
5
6
Order By: Relevance
“…2,4,6,11,12,14,15,17,18,20,22,24,26,27,[29][30][31][32][33] Hospital-based and populationbased studies that demonstrated significant seasonal variation found that the peak period for SAH differed widely. [4][5][6]15,20,24,26,32,33) No statistically significant seasonal variations were also observed in some studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,6,11,12,14,15,17,18,20,22,24,26,27,[29][30][31][32][33] Hospital-based and populationbased studies that demonstrated significant seasonal variation found that the peak period for SAH differed widely. [4][5][6]15,20,24,26,32,33) No statistically significant seasonal variations were also observed in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…8,13) However, investigation of the seasonal incidence of SAH has identified environmental and sociomedical factors correlated with aneurysm rupture. 2,4,6,11,12,14,15,17,18,20,22,24,26,27,[29][30][31][32][33] The present study investigated the relationship between sex and seasonal occurrence of SAH.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Many studies have demonstrated an increased incidence of acute cardiovascular events in winter compared with other seasons. Blood pressure (BP) has also been reported to be higher in winter than in the other three seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Keywords: ambulatory blood pressure monitoring; cold pressure stress; outdoor temperature; prewaking morning blood pressure surge INTRODUCTION Previous studies have indicated that the onset of cardiovascular events show circadian, weekly and seasonal variations. [1][2][3] Many studies have demonstrated an increased incidence of acute cardiovascular events in winter compared with other seasons. Blood pressure (BP) has also been reported to be higher in winter than in the other three seasons.…”
mentioning
confidence: 99%
“…Palavras-chave: acidente vascular cerebral, temperatura, risco cardiovascular, sazonal. The correlation between strokes and seasonal variations have been studied in various places [1][2][3][4][5][6][7][8] . Some studies around the world have reported an increase of incidence, mortality, and stroke hospitalization during the coldest months of winter.…”
Section: Introductionmentioning
confidence: 99%